College - Horne, James W., 1880-1942; Keaton, Buster, 1895-1966; Cornwall, Anne, 1897-1980; Joseph M. Schenck Productions; Cinetel Films ([Los Angeles, CA] : Joseph M. Schenck Productions, 1927)
Ronald is a good student, but useless at sports. He decides, however, to follow his girlfriend to college, and become an athlete. --
Originally released by United Artists.
Buster Keaton, Anne Cornwall, Snitz Edwards, Carl Harbaugh, Sam Crawford, Florence Turner.
Cinematographers, Dev Jennings and Bert Haines; editor, Sherm Kell.
Silent, with English intertitles and musical accompaniment; optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: College students -- Drama; College sports -- Drama; Silent films; Comedy films; Sports films; Internet videos; Streaming video